1974
DOI: 10.1002/bjs.1800611018
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of advanced bladder cancer with sensitized pig lymphocytes

Abstract: Twenty‐five patients with transitional cell carcinoma of the urinary bladder have been treated by infusion of sensitized pig lymph node cells into the arterial blood supply of the tumour. In 7 cases pig cell infusion was the only treatment, in a further 7 patients pig cells were given in the treatment of a major tumour recurrence following radiotherapy and in 11 patients pig cell infusion was followed after 4‐8 weeks by an attenuated course of radiotherapy. In these three treatment groups 2, 3 and 9 patients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

1974
1974
1999
1999

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Previous reports have described the use of cells from pig mesenteric lymph nodes, immunized against human urinary bladder carcinomata, in the treatment of these tumors (Symes et al, 1973;Feneley et al, 1974;Symes et al, 1978). In brief, fragments of tumor, obtained by transurethral resection, were implanted between the leaves of a pig mesentery.…”
Section: Introductionmentioning
confidence: 96%
“…Previous reports have described the use of cells from pig mesenteric lymph nodes, immunized against human urinary bladder carcinomata, in the treatment of these tumors (Symes et al, 1973;Feneley et al, 1974;Symes et al, 1978). In brief, fragments of tumor, obtained by transurethral resection, were implanted between the leaves of a pig mesentery.…”
Section: Introductionmentioning
confidence: 96%
“…Fourteen of 25 patients obtained clinical benefit as assessed by all of three parameters -a remission of symptoms, reduction in tumor size and histological change in the tumor (Symes et al, 1973;Feneley et al, 1974). These clinical observations raised a number of fundamental questions.…”
Section: Introductionmentioning
confidence: 97%
“…Since Mitchison [1] first reported that allo-tumor rejection was mediated by immunized lymphocytes in 1955, many clinical trials to treat human cancers by means of adoptive transfer of lymphocytes have been conducted but with little or no clinical effect [2][3][4]. In 1985, Rosenberg et al [5] introduced lymphokineactivated killer cell therapy, and the reported clinical effects surprised many clinicians.…”
Section: Introductionmentioning
confidence: 99%